Penarapan Gold for Green Building pada Gedung Perkantoran Menara Danareksa di Jakarta Pusat, Indonesia - Arinda Kamila Putri; Iwan Wibisono (Jurnal Mahasiswa Departemen Arsitektur, 2023)
Specific strategies have been developed to raise environmental awareness, also known as the "green building concept," to lessen the detrimental effects of buildings on the environment. Green construction is becoming more profitable and in demand in the global construction sector as demand for more environmentally friendly building solutions rises (USGBC, 2016). The Green Building Council Indonesia (GBCI), a member of the World GBC and the only green building organization recognized globally in Indonesia, has produced a reference standard for assessing green construction criteria known as GREENSHIP. The focus of this research is how the Gold for Green Building The specification is applied to the Menara Danareksa Office Building in Central Jakarta, Indonesia. Parameters of GREENSHIP New Building ver. 1.2 developed by GBCI was used in this study. Menara Danareksa Indonesia received 53 points from the assessment for each category. Results include Land Use Efficiency (13 points), Energy Conservation (13 points), Water Conservation (19 points), Material Cycle (2 points), Spatial Comfort (3 points), and Environmental Management (3 points). The results of this study indicate that Danareksa Tower is eligible to be declared a green building with GOLD specifications according to GBCI, with points obtained of 53 points or 69% which is appropriate at the building stage in planning.